AB1176 Juvenile systemic lupus erythematosus and anca - associated vasculitis. (23rd January 2014) - Frkovic, M.; Vukovic, J.; Mustapic, Z.; Bojanic, K.; Malenica, B.; Jelusic, M.
Abstract : Background: Systemic lupus erythematosus (SLE) is a common multisystemic autoimmune disease characterised by antibodies against nuclear components, so-called ANAs. Group of vasculitedes which are characterised by the presence of antineutrophilic cytoplasmatic antibodies (ANCA) usually affect small vessels. These two are most commonly two distinguishable pathologies and even when SLE patients develop vasculitis, they are rarely ANCA positive. On the other hand, those who are ANCA positive, usually do not develop concommitant vasculitis symptoms.Therefore, very few SLE patients have been described having both laboratory and clinical proof of ANCA vasculitis. Results: We present five patients ranging from 12 up to 17 years of age diagnosed and treated at our Department over the last 14 months (November 2010 to January 2012). All of them were diagnosed with SLE according to ACR criteria but developed ANCA positive vasculitis as well. Three of the patients were diagnosed with autoimmune hepatitis and one with lupus nephritis class V. All of them presented with fever, severe general distress and vasculitic rash. Three of the patients demonstrated hepatosplenomegaly and elevated liver function tests, and in two patients imaging confirmed retroperitoneal lymphadenopathy and laboratory tests revealed polyclonal gammopathy. They were treated with pulse methylprednisolone and pulse cyclophosphamide (6x). At present, all patients except one, are without clinical symptoms with improved immunological findings. Conclusions: We conclude that, although there is limited evidence, juvenile SLE and ANCA positive vasculitis overlap syndrome is more often than recognized. Since these patients usually present with severe clinical pattern and therefore require fast and intensive treatment, this pathology represents a topic to consider in the future. Disclosure of Interest: None Declared